2020
DOI: 10.1111/1541-4337.12522
|View full text |Cite
|
Sign up to set email alerts
|

Roadmap of cocoa quality and authenticity control in the industry: A review of conventional and alternative methods

Abstract: Cocoa (Theobroma cacao L.) and its derivatives are appreciated for their aroma, color, and healthy properties, and are commodities of high economic value worldwide. Wide ranges of conventional methods have been used for years to guarantee cocoa quality. Recently, however, demand for global cocoa and the requirements of sensory, functional, and safety cocoa attributes have changed. On the one hand, society and health authorities are increasingly demanding new more accurate quality control tests, including not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 142 publications
(244 reference statements)
0
16
0
1
Order By: Relevance
“…Chemometric methods have been implemented for characterizing key compositional markers such as volatiles, 12,100–103 fatty acids, 104 peptides, 11,67,105 bioactive compounds 82,106,107 and methylxanthines, 58,60 as well as heavy metals 56,108–111 and other contaminants 112,113 . From this perspective, a recent review on the traceability of cocoa origin has summarized and discussed destructive and nondestructive technologies providing examples aiming at assessing cocoa quality, the study of new functional properties, the detection of trace contaminants and the detection of authenticity 10 …”
Section: Authentication and Geographical Differentiation Of Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Chemometric methods have been implemented for characterizing key compositional markers such as volatiles, 12,100–103 fatty acids, 104 peptides, 11,67,105 bioactive compounds 82,106,107 and methylxanthines, 58,60 as well as heavy metals 56,108–111 and other contaminants 112,113 . From this perspective, a recent review on the traceability of cocoa origin has summarized and discussed destructive and nondestructive technologies providing examples aiming at assessing cocoa quality, the study of new functional properties, the detection of trace contaminants and the detection of authenticity 10 …”
Section: Authentication and Geographical Differentiation Of Qualitymentioning
confidence: 99%
“…However, registered geographical labels for cocoa beans are uncommon, which in part has been caused by the association between quality of chocolate and geography predominantly linked to locations of manufacturing and final transformations, rather than to cocoa beans as ingredients 7,8 . Nevertheless, a few studies have shown a strong influence on consumer perception of quality for chocolates made from origin‐labeled cocoa, 7,9 while abundant chemometric research continues to elucidate the contributions of geography to cocoa quality diversity 10–12 …”
Section: Introductionmentioning
confidence: 99%
“…The high FFA content of a cocoa bean often results from poor postharvest handling, which triggers microbial lipase to facilitate the release of fatty acids from the triglyceride in cocoa butter. Some of the known causes of high FFA (> 1.75) include beans from diseased pods, slow drying of the bean, broken beans, extended storage in damp environments, storing beans with high moisture content ( > 8%), an infestation of insect pest and general physical integrity loss of the cocoa beans [36]. In another FFA study of cocoa beans, Oyewo and Amo [37] reported that beans damaged by insects recorded higher FFA beyond acceptable limits in contrast to intact beans, but Servent et al [38] attributed FFA change to genotype and origin of the cocoa.…”
Section: Ffa and Ph Of Cocoa Beansmentioning
confidence: 99%
“…According to Quelal-vásconez and Pérez-esteve [36], flavor attributes in cocoa beans are formed from a combination of physical and chemical parameters. While the physical is mostly about the integrity of the beans, the chemical encompasses the volatile and nonvolatile compound constituents.…”
Section: F Identification Of Flavour Attributesmentioning
confidence: 99%
“…Cocoa nibs are the primary raw material used in chocolate production, and their quality determines the final satisfaction of the customers [2], [3]. Apart from raw materials and other supporting materials, processing techniques and particle size distribution significantly affect the physical, rheological properties, and organoleptic perceptions of chocolate [1].…”
Section: Introductionmentioning
confidence: 99%